One-Pot Synthesis of W2C/WS2 Hybrid Nanostructures for Improved Hydrogen Evolution Reactions and Supercapacitors - Sajjad Hussain; Iqra Rabani; Dhanasekaran Vikraman; Asad Feroze; Muhammad Ali; Young-Soo Seo; Hyun-Seok Kim; Seung-Hyun Chun; Jongwan Jung (Nanomaterials, 2020)
Tungsten sulfide (WS2) and tungsten carbide (W2C) are materialized as the auspicious candidates for various electrochemical applications, owing to their plentiful active edge sites and better conductivity. In this work, the integration of W2C and WS2 was performed by using a simple chemical reaction to form W2C/WS2 hybrid as a proficient electrode for hydrogen evolution and supercapacitors. For the first time, a W2C/WS2 hybrid was engaged as a supercapacitor electrode and explored an incredible specific capacitance of ~1018 F g−1 at 1 A g−1 with the outstanding robustness. Furthermore, the constructed symmetric supercapacitor using W2C/WS2 possessed an energy density of 45.5 Wh kg−1 at 0.5 kW kg−1 power density. For hydrogen evolution, the W2C/WS2 hybrid produced the low overpotentials of 133 and 105 mV at 10 mA cm−2 with the small Tafel slopes of 70 and 84 mV dec−1 in acidic and alkaline media, respectively, proving their outstanding interfaced electrocatalytic characteristics. The engineered W2C/WS2-based electrode offered the high-performance for electrochemical energy applications.